The Presumption of Innocence : Evidential and Human Rights Perspectives. - Stumer, Andrew; Bell, John.; Kilpatrick, Claire (London : Bloomsbury Publishing, 2010)
This book investigates the supposed justifications for limitation of the presumption of innocence by analysing its history, rationale and scope.
Prelims -- Foreword -- Table of Contents -- List of Abbreviations -- Table of Cases -- Table of Legislation -- Table of Conventions, Treaties etc. -- Introduction -- 1 The Presumption Before the HRA -- 2 Rationale for the Presumption -- 3 Scope of the Presumption -- 4 The Presumption in Strasbourg -- 5 Proportionality and the Presumption -- 6 Allocating the Burden of Proof -- Conclusion -- Bibliography -- Index.
Publisher supplied metadata and other sources.
Keywords: Comparative law; Human rights; Presumption of innocence -- Europe; Presumption of innocence -- Great Britain; Presumption of innocence; Human Rights; 0; Droits de l'homme (Droit international); 0; 0; 0; Comparative law; Human rights; Presumption of innocence; Great Britain; Europe